Filsafat Sosial Dalam Paradigma Al-qur'an: Dekonstruksi Teori Konflik Perspektif Barat - Zenrif, M. Fauzan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2002)
The objective of this study is to analyze the concepts of social philosophy in al-Qur 'an, especially the theory of conflict. By making use a ThematicallyÂ Approach, and of a Historical and Socio-Anthropological interpretation and analysis, it finds some concepts of Islamic social philosophy which has differences in confronting with a modern (Western) concept of conflict. It also finds the impact of these concepts in Islamic tradition of social transformation by the Muhammad saw era.